Dopamine Related Genes Differentially Affect Declarative Long-Term Memory in Healthy Humans - Leukel, Carla; Schümann, Dirk; Kalisch, Raffael; Sommer, Tobias; Bunzeck, Nico (Frontiers in Behavioral Neuroscience, 2020)
In humans, monetary reward can promote behavioral performance including response times, accuracy and subsequent recognition memory. Recent studies have shown that the dopaminergic system plays an essential role here, but the link to interindividual differences remains unclear. To further investigate this issue, we focused on previously described polymorphisms of genes affecting dopaminergic neurotransmission: DAT1 40bp, DAT1 30bp, DRD4 48bp and CNR1. Specifically, 669 healthy humans participated in a delayed recognition memory paradigm on two consecutive days. On the first day, male vs. female faces served as cues predicting an immediate monetary reward upon correct button presses. Subsequently, participants performed a remember/know recognition memory task on the same day and one day later. As predicted, reward increased accuracy and accelerated response times, which were modulated by DAT 30bp. However, reward did not promote subsequent recognition memory performance and there was no interaction with any genotype tested here. Importantly, there were differential effects of genotype on declarative long-term memory independent of reward: (a) DAT1 40bp was linked to quality of memory with a more pronounced difference between recollection and familiarity in the heterozygous and homozygous 10-R as compared to homozygous 9-R; (b) DAT1 30bp was linked to memory decay, which was most pronounced in homozygous 4-R; (c) DRD4 48bp was linked to overall recognition memory with higher performance in the short allele group; and (d) CNR1 was linked to overall memory with reduced performance in the homozygous short group. These findings give new insights into how polymorphisms, that are related to dopaminergic neuromodulation, differentially affect long-term recognition memory performance.